Unpacking the Relationship Between Customer (In)Justice and Employee Turnover Outcomes: Can Fair Supervisor Treatment Reduce Employees' Emotional Turmoil?. (May 2021) - van Jaarsveld, Danielle D.; Walker, David D.; Restubog, Simon Lloyd D.; Skarlicki, Daniel; Chen, Yueyang; Frické, Pascale H.
Service employees can experience considerable resource demands from customers and supervisors in their day-to-day work. Guided by the conservation of resources (COR) perspective and organizational justice research, we explored the relationship between interpersonal injustice (e.g., being treated with low dignity and respect) by customers and employee turnover (e.g., voluntary turnover, turnover intentions). Specifically, we proposed that customer interpersonal injustice relates positively to employee turnover outcomes through a process first involving employee experiences of negative emotions, and second, employee emotional exhaustion. We also examined whether supervisor interpersonal justice mitigates this process by providing emotional resources that buffer the demands of customer interpersonal injustice. We evaluated these predictions in a programmatic series of three complementary field studies involving retail employees (Study 1, N = 263), restaurant employees (Study 2, N = 206), and contact center employees (Study 3, N = 317). The results showed that (a) customer interpersonal injustice relates positively to employees' negative emotions, (b) employee negative emotions are positively associated with emotional exhaustion, and (c) emotional exhaustion relates to higher employee turnover outcomes. Our results also show that the indirect effect of customer interpersonal injustice on employee turnover intentions (Study 2) and voluntary turnover (Study 3) is weaker when employees perceive more (vs. less) supervisor interpersonal justice. Theoretical and practical implications are discussed.